Integral analysis system of training tasks, SIATE, in invasion games - Sergio José Ibáñez; Sebastián Feu; María Cañadas (Federación Extremeña de Balonmano; University of Extremadura, 2016)
The analysis of the coach intervention is carried out on objective, valid and reliable data. This information is provided of training planning and / or systematic observation. The task analysis training is essential to optimize training processes and training of athletes. For this purpose, planning and process control training is required. The SIATE is a methodological system to record and analyze the different factors that affect sports training in sports invasion, which has five characteristics: universality, standardization, modularity, flexibility and adaptability. The registration of the following factors is proposed: Contextual Data; Coach; Session; Pedagogical variables; Organizational variables; External Load; Internal load; and Kinematics variables in each training tasks. Within each factor they include and define various variables, along with the categories recorded. The SIATE provide a lot of data by coaches they will be analyzed on two levels deep, descriptive and inferential (relations and differences between variables). The integration of practical knowledge provided by SIATE and experience of coaches collaborate on professional development coach.